Exploring the Antibacterial and Antifungal Efficacy of Herbal Plants: An Ayurvedic Research - Gajapathi Balaraman; V. M. Jerbin Vijay; P. Joanna Gracy; S. Arul Kumar; S. Vishali; G. Harish (Journal of Pharmacy and Bioallied Sciences)
Context: Nature has endowed humanity with a vast repository of remedies that have been use for ages to heal all sorts of ailments. Aim: To evaluate the antibacterial and antifungal efficacy of three herbal plants (Justicia adhatoda, Glycyrrhiza glabra, and Punica granatum), on three microorganisms (Streptococcus mutans, Staphylococcus aureus, and Candida albicans) that are present in the oral stoma. Settings and Design: In vitro microbial study. Methods and Material: Extracts of 0.3 mg/ml, 0.6 mg/ml, 1.25 mg/ml, 2.5 mg/ml, 5.0 mg/ml, and 10.0 mg/ml were prepared from leaves of Justicia adhatoda, barks of Glycyrrhiza glabra, and fruits of Punica granatum, respectively. The antibacterial and antifungal efficacies of the extracts were evaluated by agar well diffusion method and their resultant zone of inhibition. Statistical Analysis Used: One-way ANOVA test and Tukey HSD post-hoc test. Results: The order of antimicrobial efficacy observed in increasing order—Glycyrrhiza glabra < Justicia adhatoda < Punica granatum. Higher the concentration of plant extract, increased the zone of inhibition. Conclusion: The extracts of Justicia adhatoda, Glycyrrhiza glabra, and Punica granatum were found to be effective against oral pathogenic microorganisms.